The effect of taking blood pressure lowering medication at night on cardiovascular disease risk. A systematic review - Ho, Chau L.B.; Chowdhury, Enayet; Doust, J.; Nelson, M.R.; Reid, Christopher (SPRINGERNATURE, 2021)
To investigate the effect of night-time BP-lowering drug treatment on the risk of major CVD and mortality, we systematically reviewed randomized controlled trials comparing night-time versus morning dosing. Two studies were found relevant to the clinical question (the MAPEC and Hygia trials). They were similar in study design and population and were conducted by the same study group. As the Hygia trial had more power with a significantly larger sample size, we did not perform a meta-analysis. Both studies reported a reduction of ~50% in major CVD events and all-cause mortality with night-time dosing and a reduction of 60% in CVD mortality. The results from these studies support the implementation of night-time BP-lowering drug treatment in the prevention of CVD and mortality. However there is an on-going discussion on the validity and methodology of MAPEC and Hygia trials, the interpretation of the results should be cautious. Stronger evidence is needed prior to changing clinical practice. Questions that remain to be answered relate to the generalisability of the results across different populations at different levels of BP related risk and the importance of morning versus evening timing of medication on CVD prevention as determined though a well-designed randomised controlled trial.